Risk Register : Implikasi Penerapan Manajemen Risiko pada CV Elang Borneo Sejahtera - Ni Komang Septia Noriska (Journal of Management and Bussines (JOMB), 2024)
Risk is something that is uncertain but always has the potential to arise in every activity, especially business activities. In the current era of global business dynamics, risk management has become a critical aspect in achieving organizational sustainability and success. This research was carried out by collecting data in the form of interviews, observations and documentation. After obtaining the data, researchers will enter it into the Risk Register. The discussion method of this research is descriptive with a quantitative approach. The conclusion is that business organizations or companies that are able to integrate risk management well in the Risk Register have a competitive advantage. Business people are able to respond to challenges and opportunities more responsively, minimize negative impacts, and even turn risks into growth opportunities. Keywords: Risk Register, Implementation, Risk Management, Rope Access